COMPARISON OF INDEPENDENT SPIKE DRILLING TRAINING AND WITH A SETTER ON IMPROVING 3-METER SPIKES FOR VOLLEYBALL ATHLETES 17-19 YEARS OLD - Ikhsan Pascal (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
The purpose of this study was to determine the effect of two forms of training that is with the drilling spike method independently with gradual distance and drilling spike with setter with Spiker Specialization attribute variables on the ability to spike 3 meters. The method used in this research is an experiment with the treatment by level 2 x 2 design. This research was conducted within the scope of the DKI Jakarta Volleyball Pengprov with a population of XX PON Pelatda athletes in DKI Jakarta Province who experienced chronic ankle sprain totaling 76 athletes with a composition of 42 athletes in the position of Outside Hitter and 34 athletes in the position of Middle Block. The sample in this study amounted to 44 people with purposive proportional random sampling technique then divided into 4 groups. The instrument used to measure 3-meter spikes in this study is the Spike Skills Test instrument. Based on the results of data processing and analysis, it can be concluded that: (1) There is a difference between drilling spike training therapy independently with gradual distance and drilling spike with setter to increase 3-meter spike, (2) There is an interaction between training therapy and spiker specialization to increase 3-meter spike, (3) There is a difference between drilling spike training independently with gradual distance to increase 3-meter spike in the group of athletes who position as Outside Hitter, 3-meter spike improvement is higher if trained spike drilling independently, (4) There is a difference between independent spike drilling training with gradual distance on 3-meter spike improvement in the group of athletes positioned as Middle Blocker, 3-meter spike improvement is higher if trained spike drilling with a setter.